Capsaicin pretreatment attenuates salt-sensitive hypertension by alleviating AMPK/Akt/Nrf2 pathway in hypothalamic paraventricular nucleus - Jia, Xiu-Yue; Yang, Yu; Jia, Xiao-Tao; Jiang, Da-Li; Fu, Li-Yan; Tian, Hua; Yang, Xin-Yan; Zhao, Xin-Yue; Liu, Kai-Li; Kang, Yu-Ming; Yu, Xiao-Jing (Frontiers in Neuroscience, 2024)
Background: Long term hypertension seriously promotes target organ damage in the brain and heart, and has increasingly become serious public health problem worldwide. The anti-hypertensive effects of capsaicin has been reported, however, the role and mechanism of capsaicin within the brain on salt-induced hypertension have yet to be elucidated. This study aimed to verify the hypothesis that capsaicin attenuates salt-induced hypertension via the AMPK/Akt/Nrf2 pathway in hypothalamic paraventricular nucleus (PVN).Methods: Dahl salt-sensitive (Dahl S) rats were used as animal model for the present study. Rats were randomly divided into four groups based on their dietary regimen (0.3% normal salt diet and 8% high salt diet) and treatment methods (infusion of vehicle or capsaicin in the PVN). Capsaicin was chronically administered in the PVN throughout the animal experiment phase of the study that lasted 6 weeks.Our results demonstrated that PVN pretreatment with capsaicin can slow down raise of the blood pressure elevation and heart rate (HR) of Dahl S hypertensive rats given high salt diet. Interestingly, the cardiac hypertrophy was significantly improved. Furthermore, PVN pretreatment with capsaicin induced decrease in the expression of mRNA expression of NADPH oxidase-2 (NOX2), inducible nitric oxide synthase (iNOS), NOX4, p-IKKβ and proinfammatory cytokines and increase in number of positive cell level for Nrf2 and HO-1 in the PVN of Dahl S hypertensive rats. Additionally, the protein expressions of phosphatidylinositol 3-kinase (p-PI3K) and phosphorylated protein kinase-B (p-AKT) were decreased, phosphorylated adenosine monophosphate-activated protein kinase (p-AMPK) were increased after the PVN pretreatment with capsaicin.Capsaicin pretreatment attenuates salt-sensitive hypertension by alleviating AMPK/Akt/iNOS pathway in the PVN.